Anthracnose on postharvest avocado caused by Colletotrichum kahawae subsp. ciggaro in South Korea. Issue 4 (1st October 2020) - Kwon, Jin-Hyeuk; Choi, Okhee; Lee, Yeyeong; Kim, Seunghoe; Kang, Byeongsam; Kim, Jinwoo
Abstract: Anthracnose was observed on postharvest avocados ( Persea americana ) in a commercial market in Jinju, South Korea, in 2019. Symptoms included soft rot and sunken lesions leaking necrotic fluid. Orange conidial masses were observed on the outer surfaces of these unappealing avocados. Colletotrichum fungi producing grey to olive colonies with orange conidial masses were consistently recovered from the lesions on the avocados. The aim of this study was to isolate and identify the causative pathogen. Koch's postulates were completed by conducting pathogenicity tests on avocado fruit and wounded green Arabica coffee ( Coffea arabica ) berries. The symptoms induced artificially on avocado fruit were the same as those of the original infections, whereas negative control avocados were asymptomatic. The fungus associated with this anthracnose produced lesions on wounded coffee berries, but not on unwounded berries. Using morphological characterization, pathogenicity testing, and partial sequencing of the internal transcribed spacer (ITS) rDNA region and the glutamine synthetase ( GS ) gene, the fungus was identified as Colletotrichum kahawae subsp. ciggaro B. Weir & P.R. Johnst. The results of this study are expected to provide important information for avocado transportation and quarantine.